2020
DOI: 10.21203/rs.3.rs-25714/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of topical breast milk versus dry cord care on umbilical cord separation, complications and cord colonization

Abstract: Introduction: Neonatal death due to infections is still a great concern worldwide. Umbilical cord related infections play significant role in the neonatal mortality specially in very low birth weight infants, mother chorioamnionitis and premature rupture of membranes. It is associated with umbilical colonization, delayed separation and poor hygiene. In the current study, effect of topical breast milk usage with dry cord care on separation time, complications and colonization were compared. Methods This is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…17,18 These organisms were presented by other authors as well. 19 Ozdemir et al, who evaluated the effect of different antiseptics on cord separation time, also showed that chlorhexidine application was the most effective agent in decreasing colonization, as it significantly increased cord separation time. 20 In a study by Azza A et al, 21 2 swab samples were taken, baseline swab was taken soon after birth within 3 hours of life and 2nd swab on third day of life.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 These organisms were presented by other authors as well. 19 Ozdemir et al, who evaluated the effect of different antiseptics on cord separation time, also showed that chlorhexidine application was the most effective agent in decreasing colonization, as it significantly increased cord separation time. 20 In a study by Azza A et al, 21 2 swab samples were taken, baseline swab was taken soon after birth within 3 hours of life and 2nd swab on third day of life.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality in children less than one month is still crucial in neonatal care systems, contributing deaths of about 1.6 million per year in still developing countries (Armanian, Barekatain et al 2020). This health concern is more serious in developing countries the fact that the mortality burden seen in the rst ten days of life is estimated at about 42 percent (Armanian, Barekatain et al 2020). An umbilical stump that has just separated is known to be the best route for bacterial entrance leading to development of serious infections (Armanian, Barekatain et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This health concern is more serious in developing countries the fact that the mortality burden seen in the rst ten days of life is estimated at about 42 percent (Armanian, Barekatain et al 2020). An umbilical stump that has just separated is known to be the best route for bacterial entrance leading to development of serious infections (Armanian, Barekatain et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation